Localization and characterization of proenkephalin-A as a potential biomarker for kidney disease in murine and human kidneys - Fuchs, Michaela Alexandra Anna; Schrankl, Julia; Wagner, Charlotte; Daniel, Christoph; Kurtz, Armin; Broeker, Katharina Anna Elisabeth (Biomarkers, 2022)
Introduction: Exact measurement of renal function is essential for the treatment of patients. Elevated serum-creatinine levels, while established, are influenced by other parameters and show a significant time-lag. This drives the search for novel biomarkers of renal function and injury. Beside Lipocalin-2 and kidney-injury-molecule-1 (KIM-1), the endogenous opioid precursor proenkephalin-A (Penk) has recently emerged as a promising marker for renal function. But the cellular origin and regulation of Penk outside the brain has not yet been investigated in depth. Materials and methods: This study characterizes the cellular origin of Penk expression with high-resolution in situ hybridization in two models of renal fibrosis in mice and human tissue. Results: Interstitial cells are the main expression site for renal Penk. This classifies Penk as biomarker for interstitial damage as opposed to tubular damage markers like Lipocalin-2 and KIM-1. Furthermore, our data indicate that renal Penk expression is not regulated by classical profibrotic pathways. Discussion: This study characterizes changing Penk expression in the kidneys. The similarity of Penk expression across species gives rise to further investigations into the function of Penk in healthy and injured kidneys. Conclusion: Penk is a promising biomarker for interstitial renal damage that warrants further studies to utilize its predictive potential.Clinical significance Knowledge of real-time renal function is essential for proper treatment of critically ill patients and in early diagnosis of acute kidney injury (AKI). Proenkephalin-A has been measured in a number of patient cohorts as a highly accurate and predictive biomarker of renal damage. The present study identifies Penk as a biomarker for interstitial damage in contrast to the tubular biomarkers such as Lipocalin-2 or KIM-1. Our data show that Penk is regulated independently of classical profibrotic or proinflammatory pathways, indicating it might be more robust against extra-renal influences. Data presented in this study provide fundamental information about cell type-specific localization and regulation of the potential new biomarker Penk across species as foundation for further research.
CRIS-Team Scopus Importer:2022-12-02
Keywords: chronic kidney disease; interstitial fibrosis; kidney damage; Proenkephalin-A; renal function